Aquarium in Question. Pushing the limits of the aquatic realm within the urban environment - Grigorieva, Anna (project baikal, 2016)
In April 2016, arch out loud announced the winners of the international architectural competition, the task of which was to design NYC AQUARIUM & PUBLIC WATERFRONT. The first place was occupied by NYC AQUATRIUM designed by Italian architects.
Keywords: New York City; East River; Aquatrium; architectural competition